Impact of Fasting Status on the Use of Klotho as a Biomarker. (4th February 2021) - Paquette, Jean-Sébastien; Gerard, Ngueta; Djade, Codjo Djignefa; Cadrin-Chênevert, Alexandre; Martel, Elise; Boudreault, Samuel; Pelletier, Mathieu
Abstract: Background: Klotho is a protein secreted physiologically in humans. It acts like a hormone that regulates many biological processes. It is also a novel serological biomarker that is increasingly used as a predictive factor for several physiological and psychological conditions. Surprisingly, there is no consensus about the fasting state of the patient who is tested for klotho. Most studies are done on fasting patients, although others are done without concern about fasting status. There is a lack of evidence about this variable in klotho serological testing. Performing fasting tests on patients can be deleterious and can affect compliance. We investigated the effect of fasting status on klotho serological value. Methods: We conducted an observational study in which klotho serology was evaluated in a fasting state and 2 h after a meal. In total, 35 participants came to the laboratory without having eaten for 10 h. Blood samples were taken on arrival at our laboratory and 2 h after eating a standardized meal. Results: The mean age of our participants was 32.7 years old. There were 13 men and 22 women. In the fasting state, the klotho value was 1060.5 pg/mL (SD: 557.5 pg/mL). At 2 h after the meal, the klotho value was 1077.5 pg/mL (SD: 576.9 pg/mL). Statistical tests showed no difference before and after a meal in our study ( P  = 0.2425). Conclusions: Our results suggest that it is not necessary to perform klotho serology in a fasting state.